Seed development and its relationship to fruit structure in species of Bromelioideae (Bromeliaceae) with fleshy fruits - Silva, Kleber Resende [UNESP]; Stützel, Thomas; Oriani, Aline [UNESP] (Oxford University Press (OUP), 2020)
In Bromeliaceae, fruit type and seed morphology have been used to distinguish the subfamilies. We studied seed and fruit development of three species of Bromelioideae (Aechmea bromeliifolia, Billbergia distachia and Neoregelia bahiana) relating seed characters to fruit structure. Aechmea bromeliifolia has few ovules per locule inserted within the apical portion of the ovary and the seeds are larger, with a long chalazal appendage, growing towards the fruit base. In B. distachia and N. bahiana, the ovules are numerous and subapically to centrally inserted in the ovary; the seeds are smaller, with a radial disposition, and the chalazal appendages are short (B. distachia) or absent (N. bahiana). The chalazal appendages grow during seed development, and thus their presence/length may be related to the number of ovules/seeds per locule and to the disposition of the ovules inside the locules. The fruits are berries, and juiciness is promoted by mesocarp cells and by substances secreted inside the locules by the placental obturator at later stages of fruit development. These fruit and seed features are strategies for zoochory and provide evidence that each species studied is dispersed by a different type of animal.
Keywords: chalazal appendage; fruit anatomy; mucilaginous seed coat; secretory obturator; seed anatomy; septal nectary